An Analysis of Customer’s Satisfaction Level to the Quality of Services Provided by Regional Water Supply Company (PDAM) of Kolaka Regency - Niar Astaginy (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2017)
The study is devoted to identifying the customer’s expectation for the service quality of the regional water supply company (PDAM) of Kolaka Regency, describing the customer’s perception of its service quality, and projecting the managerial implication to improve the quality of its services. The analysis methods used are conformity level analysis and important performance analysis. The analysis indicates that the highest expectation of the customer rests on the continuous supply of water without rotation system. The best performance of the company in the customer’s perception is in the explanation of the water system installation procedure which is simple and uncomplicated. Based on Important Performance Matrix, it is apparent that quadrant 1 (Primary priorities) has eight attributes, quandrant 2(maintained) has six attributies, quandrant 3(low priority) has four attributies and quandrant 4(excessive) has two attibuties